Alginate/Poly(γ-glutamic Acid) Base Biocompatible Gel for Bone Tissue Engineering. (4th October 2015) - Chan, Wing P.; Kung, Fu-Chen; Kuo, Yu-Lin; Yang, Ming-Chen; Lai, Wen-Fu Thomas
Abstract : A technique for synthesizing biocompatible hydrogels by cross-linking calcium-form poly( γ -glutamic acid), alginate sodium, and Pluronic F-127 was created, in which alginate can be cross-linked by Ca 2+ from Ca– γ -PGA directly and γ -PGA molecules introduced into the alginate matrix to provide pH sensitivity and hemostasis. Mechanical properties, swelling behavior, and blood compatibility were investigated for each hydrogel compared with alginate and for γ -PGA hydrogel with the sodium form only. Adding F-127 improves mechanical properties efficiently and influences the temperature-sensitive swelling of the hydrogels but also has a minor effect on pH-sensitive swelling and promotes anticoagulation. MG-63 cells were used to test biocompatibility. Gelation occurred gradually through change in the elastic modulus as the release of calcium ions increased over time and caused ionic cross-linking, which promotes the elasticity of gel. In addition, the growth of MG-63 cells in the gel reflected nontoxicity. These results showed that this biocompatible scaffold has potential for application in bone materials.